A generalized differential quadrature algorithm for simulating magnetohydrodynamic peristaltic flow of blood‐based nanofluid containing magnetite nanoparticles: A physiological application. Issue 3 (27th November 2020) - Ashraf, Muhammad Usman; Qasim, Muhammad; Wakif, Abderrahim; Afridi, Muhammad Idrees; Animasaun, Isaac L.
Abstract: In this article, the peristaltic flow of blood‐based nanofluid is examined numerically by employing the generalized differential quadrature method. The Casson constitutive model is adopted to depict the flow characteristics in a uniform wavy tube. Besides, the non‐Newtonian nature and heat transfer feature of the nanofluidic medium are also scrutinized properly in the presence of platelet magnetite nanoparticles Fe3 O4 . After deriving the governing conservation equations, the resulting flow model is modeled successfully under the realistic assumptions of long wavelength and low Reynolds number. Also, the experimentally tested correlations related to the thermophysical properties of nanofluids are incorporated in the conservation equations to explore the effect of adding magnetite nanoparticles in the biofluidic medium. Mathematically, the obtained partial differential equations are transformed into the dimensionless form by utilizing feasible transformations. Furthermore, the impacts of sundry physical parameters on the trapping phenomena, pressure gradient, velocity, wall shear stress, and temperature are discussed thoroughly for the present MHD non‐Newtonian nanofluid flow model via various displays.